A Magnetically Coupled Dielectric Elastomer Pump for Soft Robotics. Issue 8 (17th May 2019) - Cao, Chongjing; Gao, Xing; Conn, Andrew T.
Abstract: Fluidic elastomer actuators have become ubiquitous in soft robotics as they can be used to create inherently compliant systems with embodied intelligence. However, they typically use conventional rigid air‐compression systems that restrict their application in untethered mobile and wearable devices. An embeddable pneumatic diaphragm pump is presented for soft robotics driven by a magnetically coupled dielectric elastomer actuator (MCDEA). The MCDEA pump exploits a compliant coupling between membranes to resonate at high power and efficiency despite the damping effects of the pneumatic chamber and valves. The MCDEA pump demonstrates an attractive dynamic performance with a peak stroke at resonance of over 800% of that at low frequencies, which corresponds to a maximum output pressure of 30.5 mbar and a flowrate of 0.9 L min −1 at a relatively low power consumption of 40 mW. The performance of this pneumatic pump design is demonstrated by integrating it with several soft robotic prototypes, including a soft gripper, ballooning chamber, and a suction cup. It shows considerable promise for driving the next generation of fully compliant and untethered soft robots. Abstract : A pneumatic diaphragm pump driven by a magnetically coupled dielectric elastomer actuator is developed. It exploits a compliant coupling between membranes to resonate at high power and efficiency. The pump generates a maximum output pressure of 30.5 mbar and flowrate of 0.9 L min −1 . It is demonstrated driving soft robotic prototypes including a soft gripper, ballooning chamber, and suction cup.